Boys lagging behind: Unpacking gender differences in academic achievement across East Africa. (May 2021) - Buhl-Wiggers, Julie; Jones, Sam; Thornton, Rebecca
Highlights: We investigate gender disparities in academic achievement across Kenya, Tanzania and Uganda. On average girls outperform boys in both literacy and numeracy. To avoid confounding factors we include household fixed effects and address differential selection into school. Intra-generational transmission of education is an important explanatory factor. The gender gap is geographically clustered and even reversed in some districts. Abstract: We estimate the current magnitude of gender gaps in literacy and numeracy in Kenya, Tanzania and Uganda, using large-scale nationally representative data of children ages 6–16. Using a household fixed effects approach, we document that girls outperform boys in all three countries; in numeracy by 0.03 SDs (Uganda) to 0.05 SDs (Kenya and Tanzania) and literacy by 0.06 SDs (Uganda and Tanzania) to 0.09 SDs (Kenya). However, the gender gap in achievement is highly geographically clustered, reversing in sign in some districts. In highlighting the heterogeneity of gender disparities in academic performance in these three countries in East Africa, this study show that systematic female disadvantage in schooling is no longer the norm.